Possibilities and limitations of digital microscopy of blood smear of the modern hematological analyzer Sysmex XN-3100 in leukocyte differentiation: Digital microscopy for leukocyte differentiation - Klapuh-Bukvić, Nermina (Journal of Medical Biochemistry, 2025)
Background: Differentiation of leukocytes is one of the key diagnostic procedures in clinical medicine and their correct identification in a blood smear is of essential importance. Light microscopy is the reference method for leukocyte differentiation, however, it is time-consuming, and it must be performed by a highly qualified specialist. For this reason, automatic analyzers capable of precise and accurate differentiation of blood cells in the examined sample are increasingly present in hematology laboratories. The aim of this paper is to evaluate the performance of Sysmex XN-3100 analyzer, manufactured by SYSMEX CORPORATION, Kobe, Japan., with focus on the advantages and disadvantages of its digital microscopy in the differentiation of leukocytes. Methods: Digital optical microscopy on 253 samples was performed with primary data (preclassification) collected after the completion of the autoanalysis. Before validating the obtained results, the data were reviewed by a medical biochemistry specialist who confirmed or corrected it. This generated secondary data (reclassification). The two groups of data were statistically analyzed using Passing-Bablok regression analysis, Bland-Altman analysis and Spearman correlation. Results: The obtained results showed strong correlations between the primary and secondary analysis in all cells (highest in lymphocyte group (r=0.986), lowest in eosinophil group (r=0.870)) except immature granulocytes and blasts (significant deviation from linearity, p<0.01). Conclusions: Hematology analyzer Sysmex XN-3100 shows high performance in leukocyte analysis and differentiation using digital microscopy, but samples containing blasts and immature granulocytes must be additionally analyzed by light microscopy.